Pyrrolidine dithiocarbamate sensitizes U251 brain glioma cells to temozolomide via downregulation of MGMT and BCL-XL - Tang, Jun-Hai (Oncol Lett, 2017)
The current study investigated the effect of pyrrolidine dithiocarbamate (PDTC) on the proliferation, apoptosis, cell cycle and sensitivity to temozolomide (TMZ) of the U251 glioma cell line. Proliferation, apoptosis and cell cycle analysis of U251 cells following treatment with PDTC and TMZ was determined by an MTT assay and flow cytometry, respectively. The mRNA and protein expression levels of O-6-methylguanine-DNA methyltransferase (MGMT), B-cell lymphoma extra-large (BCL-XL) and survivin were further determined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting analysis. The results revealed that treatment with TMZ, PDTC and TMZ + PDTC significantly inhibited cell proliferation, induced apoptosis and contributed to cell cycle arrest in U251 cells. A combination of PDTC and TMZ induced the highest rates of proliferation inhibition and apoptosis. PDTC treatment markedly reduced the expression levels of MGMT, BCL-XL and survivin. The expression levels of MGMT and BCL-XL, were significantly upregulated by TMZ but not by combination treatment of TMZ and PDTC. The results of the present study suggest that treatment with PDTC inhibits cell proliferation, induces apoptosis and cell cycle arrest, and enhances sensitivity to TMZ in U251 cells, which is partly induced by downregulation of MGMT and BCL-XL.